Physiological and Biochemical Response of Wild Olive (Olea europaea Subsp. europaea var. sylvestris) to Salinity - Tadić, Josip; Dumičić, Gvozden; Veršić Bratinčević, Maja; Vitko, Sandra; Radić Brkanac, Sandra (Frontiers in Plant Science, 2021)
In the face of climate change, water deficit and increasing soil salinity pose an even greater challenge to olive cultivation in the Mediterranean basin. Due to its tolerance to abiotic stresses, wild olive (Olea europaea subsp. europaea var. sylvestris) presents a good candidate in breeding climate-resilient olive varieties. In this study, the early response of the native Croatian wild olive genotype (WOG) to salinity was evaluated and compared to that of well-known cultivars (cv.) Leccino and Koroneiki. Potted olive plants were exposed either to 150 mM NaCl or 300 mM mannitol for three weeks with the aim of distinguishing between the osmotic and ionic components of salt stress. To determine the impact of plant age on salinity, one-, two- and three-year-old WOG plants were used in the study. Growth parameters of both cultivars and WOG of different age decreased in response to mannitol treatment. In contrast to cv. Leccino, NaCl treatment did not significantly affect the growth of cv. Koroneiki or WOG of any age. Contents of Na+ and Cl- were considerably higher in salt-treated WOG regardless of age, compared to the cultivars. However, while both treatments significantly reduced the K+ content of cv. Koroneiki, that nutrient was not significantly affected in either cv. Leccino or WOG. Unlike the cultivars and older WOG, NaCl treatment caused a significant decline of photosynthetic pigments in one-year-old WOG. The cultivars and WOG of different age experienced a similar drop in chlorophyll a content under isotonic mannitol treatment. The absence of lipid peroxidation, modulation of superoxide dismutase and guaiacol peroxidase activity was noted in all WOG ages under both stressors. These data suggest that WOG resilience to salinity is associated with its large leaf capacity for Na+ and Cl- accumulation, K+ retention, and its adaptable antioxidative mechanisms. The results are promising with regard to obtaining a new olive cultivar with better resilience to soil salinity.